Plant developmental oddities - Carlo M. Pozzi; Vittoria F. Brambilla; Angelo Gaiti; Alberto Spada (Planta, 2024)
Main conclusion Plants lacking shoot apical meristem develop with unique body shapes, suggesting rewiring of developmental genes. This loss of the meristem is likely influenced by a combination of environmental factors and evolutionary pressures. Abstract This study explores the development of plant bodies in three families (Podostemaceae, Lemnaceae, and Gesneriaceae) where the shoot apical meristem (SAM), a key structure for growth, is absent or altered. The review highlights alternative developmental strategies these plants employ. Also, we considered alternative reproduction in those species, namely through structures like turions, fronds, or modified leaves, bypassing the need for a SAM. Further, we report on studies based on the expression patterns of genes known to be involved in SAM formation and function. Interestingly, these genes are still present but expressed in atypical locations, suggesting a rewiring of developmental networks. Our view on the current literature and knowledge indicates that the loss or reduction of the SAM is driven by a combination of environmental pressures and evolutionary constraints, leading to these unique morphologies. Further research, also building on Next-Generation Sequencing, will be instrumental to explore the genetic basis for these adaptations and how environmental factors influence them.